Comparative analysis of outdoor energy harvest of organic and silicon solar modules for applications in BIPV systems - Feroze, Sarmad; Distler, Andreas; Forberich, Karen; Ahmed Channa, Iftikhar; Doll, Bernd; Brabec, Christoph; Egelhaaf, Hans-Joachim (Solar Energy, 2023)
Organic photovoltaics (OPV) have the potential to fill niches that traditional silicon photovoltaics (Si-PV) have left open so far. Building-integrated photovoltaics (BIPV) is one key area where OPV modules can play a vital role due to their functional attributes of semitransparency, flexibility, and lightweight. However, the architectural constraints and physical layout of buildings often do not allow the installation of photovoltaic (PV) modules at their optimal angles. Herein, we report the outdoor energy harvest of commercial OPV, and monocrystalline silicon (m-Si) modules mounted at inclinations of 45° and 90°, using the ISOS-O2 protocol as a test standard. The semitransparent OPV modules incorporating a P3HT:PCBM bulk heterojunction absorbing layer were found to offer daily specific energy yields (YF) that are 10–15% higher than those of the m-Si modules at 45° inclination. For vertical (90°) mounting, the YF of the OPV modules is even 24–30% higher than that of their inorganic counterparts, thus making them ideally suited for façade integrated BIPV. Laboratory investigations reveal that the superior performance of OPV modules in the vertical position is mainly due to a strongly enhanced fill factor (FF) at reduced in-plane irradiance. At a 45° inclination, the positive temperature coefficient of the OPV modules also plays an important role during high-irradiance hours.
CRIS-Team Scopus Importer:2023-09-22
Keywords: Building-integrated photovoltaics; Energy harvest; Organic photovoltaics; Outdoor monitoring

Fassadenelemente mit organischer Photovoltaik - Egelhaaf, Hans-Joachim; Brabec, Christoph; Neberich, Marcel; Senguttuvan, Kaushik; Hoga, Felix; Kießling, Günther; Braun, Matthias; Bordin, Susanna; Wagner, Michael; Distler, Andreas; Feroze, Sarmad; Dentel, Arno (BWK Das Energie Fachmagazin, 2021)
In dem vom Bundesministerium für Wirtschaft und Energie (BMWi) geförderten Projekt „Fassade3“ entwickelt ein Konsortium aus akademischen und industriellen Partnern ein multifunktionales Fassadenelement mit integrierter organischer Photovoltaik (OPV). Die Fassade kann aufgrund ihrer modularen Struktur vorgefertigt und sowohl in Neu- als auch Bestandsgebäude integriert werden. Sie fungiert als Energiequelle, dient der thermischen Isolation, bietet Sonnenschutz für den Innenraum und optimiert so die Energieeffizienz des Gebäudes. Mit einfachen Mitteln lässt sich somit eine voll funktionsfähige und gleichzeitig ästhetisch ansprechende Konstruktion realisieren. Ein eigens entwickeltes Messsystem erlaubt die Echtzeit-Überwachung der Energiebilanz der Fassade. Erste Ergebnisse zum Leistungsverhältnis der OPV-Module sind vielversprechend.

Fully printed flexible perovskite solar modules with improved energy alignment by tin oxide surface modification - Dong, Lirong; Qiu, Shudi; García Cerrillo, José; Wagner, Michael; Kasian, Olga; Feroze, Sarmad; Jang, Dongju; Li, Chaohui; Le Corre, Vincent Marc; Zhang, Kaicheng; Peisert, Heiko; U. Kosasih, Felix; et al. (Energy and Environmental Science, 2024)
Fully printed flexible perovskite solar cells (f-PSCs) show great potential for the commercialization of perovskite photovoltaics owing to their compatibility with high-throughput roll-to-roll (R2R) production. However, the challenge remains in the deficiency in controlling interfacial recombination losses of the functional layer, causing remarkable loss of power conversion efficiency (PCE) in industrial production. Here, a fullerene-substituted alkylphosphonic acid dipole layer is introduced between the R2R-printed tin oxide electron transport layer and the perovskite active layer to reduce the energetic barrier and to suppress surface recombination at the buried interface. The resulting f-PSCs exhibit a PCE of 17.0% with negligible hysteresis, retain 95% of their initial PCE over 3000 bending cycles and achieve a T95 lifetime of 1200 h under 1 sun and 65 °C in nitrogen atmosphere. Moreover, the fully printed flexible perovskite solar mini-modules (f-PSMs) with a 20.25 cm2 aperture area achieve a PCE of 11.6%. The encapsulated f-PSMs retain 90% of their initial PCE after 500 h damp-heat testing at 65 °C and 85% relative humidity (ISOS-D3). This work marks an important progress toward the realization of efficient and stable flexible perovskite photovoltaics for commercialization.
CRIS-Team Scopus Importer:2024-08-16

Long term outdoor performance evaluation of printed semitransparent organic photovoltaic modules for BIPV/BAPV applications - Feroze, Sarmad; Distler, Andreas; Dong, Lirong; Wagner, Michael; Channa, Iftikhar Ahmed; Hoga, Felix; Brabec, Christoph; Egelhaaf, Hans-Joachim (Energy and Environmental Science, 2024)
Recently, organic photovoltaics (OPV) have achieved power conversion efficiencies (PCE) above 20% thus coming closer to market entry. Building-integrated photovoltaics (BIPV) and building-attached photovoltaics (BAPV) are two key areas where the functional advantages of both OPV and BIPV/BAPV complement each other and thus could pave the way for market penetration of OPV. Herein, we report on large-area, all-solution-processed flexible OPV modules manufactured by a fully roll-to-roll (R2R) method with high levels of process repeatability. The OPV modules show an accelerated lifetime (ALT) of more than 1000 h and 2800 h under the ISOS-L2 and ISOS-D3 testing conditions, respectively. Long-term outdoor monitoring of the OPV modules was conducted in a typical central European climate, considering two distinct mounting angles that hold significant relevance for BIPV installations i.e., 45° inclination with respect to the ground (representing the optimal tilt angle of the site) and 90° vertical mounting (as mostly encountered in BIPV façades). The ISOS-O2 protocol was used as the test standard for outdoor monitoring. The results show that the OPV modules can offer higher daily specific energy yields (YFD), i.e., higher ratios of daily energy yield and STC WP capacity of the module, than a reference mono-crystalline (m-Si) module for BIPV installations typical of a rooftop case (i.e., 45°), whereas for façade integrated cases (i.e., 90°), OPV modules offer YFD values identical to that of m-Si modules. Detailed laboratory investigations reveal that the higher YFD values of the OPV modules at 45° mounting stems from their negligible temperature coefficient of −0.008% °C−1, whereas at 90° mounting, the angle-dependent response of the modules plays a crucial role.
CRIS-Team Scopus Importer:2025-02-04

Roll-to-Roll Deposition of Wide-Bandgap CsFAPbBr3 Perovskite Solar Cells in Ambient Air with Optimized Ink Formulation - Jafarzadeh, Farshad; Dong, Lirong; Jang, Dongju; Wagner, Michael; Koch, Giulio; Qiu, Shudi; Feroze, Sarmad; García Cerrillo, José; Brabec, Christoph; Di Carlo, Aldo; Brunetti, Francesca; Egelhaaf, Hans-Joachim; et al. (Solar RRL, 2024)
The growing demand for sustainable energy solutions has made the development of scalable, efficient, and cost-effective perovskite solar cells (PSCs) increasingly important. Wide-bandgap perovskites (WB-PSCs) stand out due to their efficiency in low-light conditions and their use in tandem solar cells. WB-PSCs are currently behind conventional PSCs in upscaling, with limited success in printing wide bandgap PSCs. Developing upscaling methods is essential to fully realize their potential in the renewable energy sector. This research addresses the development of roll-to-roll (R2R) slot-die coating of Cs0.05FA0.95PbBr3-based WB-PSCs by focusing on improving the film formation process and ink formulation. By adding optimal concentration of CsBr and performing in situ characterization, we obtained Cs0.05FA0.95PbBr3 films with enhanced morphology and crystallinity in ambient conditions (50% RH), without inducing secondary phase formation. In addition, slot-die coating defects are eliminated through introducing DMSO: Butanol (9:1) solvent system. The R2R coated wide-bandgap PSCs reaches a power conversion efficiency (PCE) of up to 8.97% under 1-sun conditions and 18.3% PCE under indoor conditions. The corresponding R2R coated modules with a 5 × 5 cm2 active area achieve a PCE of 5.8%, representing a crucial step towards the high-throughput, cost-effective production of perovskite solar modules.
CRIS-Team Scopus Importer:2024-10-11
Keywords: ambient deposition; ink formulation; roll-to-roll; slot-die coating; wide-bandgap perovskite solar cells

Simplifying contact-layer design for high-throughput printing of flexible perovskite photovoltaics - Dong, Lirong; Qiu, Shudi; Feroze, Sarmad; Wagner, Michael; Kasian, Olga; Peisert, Heiko; Kosasih, Felix U.; Ducati, Caterina; García Cerrillo, José; Tian, Jingjing; Li, Chaohui; Jang, Dongju; et al. (Energy and Environmental Science, 2024)
The realization of scalable roll-to-roll production processes for metal-halide perovskite modules is a necessary development for transferring developments and technologies from the lab to the fab. Before that, it is imperative to close the efficiency gap not only between the devices fabricated on rigid substrates versus flexible substrates, but also between solar cells to solar modules. In this regard, a critical assessment of device architectures that are more compatible to scalable fabrication is needed. Obviously, the adaption to mass manufacturing must not negatively impact device performance and operational stability. Here, by investigating the properties of printed fullerene-based phosphonic acid dipole interface layers, we establish simplified self-assembled monolayer (SAM) based n-i-p architectures without any charge extraction layers other than SAMs, which are easily processed and are thus ideally suited for mass production. We show that a contact-layer design with a printed fullerene-based SAM that has phosphonic acid is sufficient to provide good charge selectivity and to minimize interface recombination at the bottom electrode. We further show that the same SAM molecule can be used as a p-type interface material on top of the perovskite. This simplified contact-layer design, which is based on one material for both hole and electron work-function adaption is successfully integrated into our fully printed module process comprising the deposition of a carbon top electrode. The achieved open-circuit voltage exceeds 1.1 V, and the fill factor surpasses 70%, highlighting the potential of this novel interface design concept for both rigid and flexible substrates.
CRIS-Team Scopus Importer:2024-09-06